Data on amnesic shellfish poisons (asp) in bivalves at some aquaculture areas in the northern coastal waters of Vietnam - Minh Hien, Nguyen Thi; Thuoc, Chu Van; Ogata, Takehiko (Academia Journal of Biology, 2014)
In the framework of national project coded KC.09-19 (2004-2005), a study on the accumulation of ASP toxin in bivalves (clam and green mussel) at some aquaculture areas in the northern coastal waters of Vietnam had been carried out. The study results showed that the accumulation of ASP toxin concentration on viscera tissues of clam and green mussel at Doson, Catba, Tienhai, Langco areas usually fluctuate by time not strongly in 2004-2005. Of which the average concentration of ASP toxin per month in Do Son clam was the lowest, and ranged from 0.005 to approximately 2 ng/g tissue. The concentration of ASP toxin detected in clam and mussel tissues in the sampling areas were still lower than the permit limit and safety for consumer. There was the relationship between concentration of ASP toxin and biomass of Pseudo-nitzschia diatom at the sampling areas although it was not clearly. The accumulation of toxin in shellfish tissue depend on the toxin accumulation capacity and depuration of each shellfish species, on Pseudo-nitzschia biomass and toxin produce capacity of toxic phytoplankton species under the effect of environmental factors in each sampling area as well.